Strengthening the Legal Awareness of Kodingareng Fishermen as a Strategy for Preventing Crime in Fishing (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to strengthen legal awareness among Kodingareng fishers through community-based legal education tailored to their social characteristics and work structures. The program was implemented through initial mapping, participant segmentation based on local fishing typologies—papekang, papattek, and pagae—and dialogical legal education linked directly to everyday fishing practices. The educational content focused on clarifying categories of prohibited acts, legal consequences, and individual responsibility within both independent fishing and vessel-based collective work. The results indicate an improvement in participants’ ability to articulate legal boundaries, assess legal risks based on specific actions, and understand the relationship between legal compliance, resource sustainability, and household livelihood stability. Although economic pressure, long working hours, and patron–client relations remain significant constraints on rapid behavioral change, the enhancement of legal awareness represents a meaningful outcome within the framework of community service. The findings suggest that community-based legal education can function as an effective preventive strategy against fishing-related crimes and provide a foundation for sustained legal empowerment initiatives in small island communities.